Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ejhf.194
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomally integrated human herpesvirus 6 in heart failure: prevalence and treatment

Abstract: Aims Human herpesvirus 6 (HHV‐6) A and B are two betaherpesviruses that are associated with many conditions including roseola, drug‐induced hypersensitivity syndrome, limbic encephalitis, and myocarditis. HHV‐6 is integrated in the germline [chromosomically integrated HHV‐6 (ciHHV‐6)] in ∼0.8% of the human population. To date, the prevalence, species distribution, and treatment responses of ciHHV‐6 are unknown for cardiac patients. Methods and results We determined the prevalence of HHV‐6 and ciHHV‐6 genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 34 publications
1
56
0
2
Order By: Relevance
“…Consequently, patients with ciHHV-6 have very high DNAemia (>10 5 genomes per milliliter) if measured in whole blood. The clinical significance of ciHHV-6 in transplant recipients has not yet been defined, and it is not known whether ciHHV-6 may reactivate and produce an active infection in patients with enhanced immunosuppression (87). One study found that liver transplant recipients with ciHHV-6 had a trend toward higher rates of acute allograft rejection compared with patients with low-level or without HHV-6 replication (83).…”
Section: Type Of Organ Transplantmentioning
confidence: 99%
“…Consequently, patients with ciHHV-6 have very high DNAemia (>10 5 genomes per milliliter) if measured in whole blood. The clinical significance of ciHHV-6 in transplant recipients has not yet been defined, and it is not known whether ciHHV-6 may reactivate and produce an active infection in patients with enhanced immunosuppression (87). One study found that liver transplant recipients with ciHHV-6 had a trend toward higher rates of acute allograft rejection compared with patients with low-level or without HHV-6 replication (83).…”
Section: Type Of Organ Transplantmentioning
confidence: 99%
“…Ganciclovir/valganciclovir Most of the patients with HHV-6-induced VHD are infected with HHV-6B (which infects endothelial progenitor cells) rather than with HHV-6A (which infects neural cells) [15,16]. It is highly probable that HHV-6 enhances pathogenicity of other viruses [15].…”
Section: Interferon Betamentioning
confidence: 99%
“…In some patients, HHV-6 virus is chromosomally integrated (ciHHV-6 -identification by repeated measurement of viral loads above 10 4 DNA copies per µg of isolated DNA in tissue or blood cells) [3,15,16]. ci-HHV-6A is probably associated with an increased risk of MC [3,15,16]. HHV-6 is not cleared by IFN or ganciclovir (herpesvirus-specific inhibitor of replication) [16].…”
Section: Interferon Betamentioning
confidence: 99%
See 2 more Smart Citations